2012
DOI: 10.1105/tpc.112.096198
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Deficiency Antagonizes High-Temperature Inhibition of Disease Resistance through Enhancing Nuclear Accumulation of Resistance Proteins SNC1 and RPS4 in Arabidopsis

Abstract: Plant defense responses to pathogens are influenced by abiotic factors, including temperature. Elevated temperatures often inhibit the activities of disease resistance proteins and the defense responses they mediate. A mutant screen with an Arabidopsis thaliana temperature-sensitive autoimmune mutant bonzai1 revealed that the abscisic acid (ABA)-deficient mutant aba2 enhances resistance mediated by the resistance (R) gene SUPPRESSOR OF npr1-1 CONSTITUTIVE1 (SNC1) at high temperature. ABA deficiency promoted nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
120
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 76 publications
(87 reference statements)
4
120
1
Order By: Relevance
“…When the snc1-1 plants grown at 22°were sprayed with 10 mM of ABA twice a day for 3 days at 3 weeks old, these plants were much larger 2 weeks later than the snc1-1 sprayed only with buffer control ( Figure 3F). This effect is consistent with the earlier finding that ABA application decreased nuclear accumulation of SNC1 proteins (Mang et al 2012). …”
supporting
confidence: 93%
See 2 more Smart Citations
“…When the snc1-1 plants grown at 22°were sprayed with 10 mM of ABA twice a day for 3 days at 3 weeks old, these plants were much larger 2 weeks later than the snc1-1 sprayed only with buffer control ( Figure 3F). This effect is consistent with the earlier finding that ABA application decreased nuclear accumulation of SNC1 proteins (Mang et al 2012). …”
supporting
confidence: 93%
“…Our prior study on the int102 mutant finds that the TIR-NB-LRR protein SNC1 is the component that confers temperature sensitivity to disease resistance mediated by SNC1 (Zhu et al 2010). Study of another mutant int173 reveals that mutations in the ABA2 (ABA Deficient 2) gene enhanced disease resistance mediated by SNC1 and another R gene RPS4 (Resistance to Pseudomonas Syringae 4) at high temperature (Mang et al 2012).…”
Section: Isolation Of Temperature-insensitive Disease Resistance Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcellular fractionation and fluorescence spectrometry. Enrichment of plant nuclei was performed as previously described 60 . For fluorescence spectrometry, the protein solution of purified CRT1 was adjusted to a concentration of 10 mg ml À 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it was proposed that plants prioritize abiotic stress tolerance over the biotic stress response, with ABA as the molecular switch between the two responses to minimize the damage (Lee and Luan, 2012). Recently, however, contrary studies where biotic stress takes precedence have been reported (Kim et al, 2011;Mang et al, 2012;Sánchez-Vallet et al, 2012). Thus, in light of these recent developments, which revealed a rather complicated picture of multiple stress responses, we embarked on the identification of DEGs in abiotic and biotic stress environments separately and performed comparative analysis of the shared stress-responsive genes, which would provide vital clues on the causative factors behind the cross talk resulting in the observed synergistic and antagonistic regulation of known abiotic and biotic stress response pathways.…”
Section: Discussionmentioning
confidence: 99%